Компенсированная асинхронная машина с короткозамкнутым ротором - Жемеров, Г.Г.; Колесник, В.Ю. (Електротехніка і електромеханіка, 2009)
В работе рассмотрено подключение САФ параллельно АМ для улучшения пусковых характеристик и уменьшения потерь энергии. У роботі розглянуто підключення САФ паралельно АМ для покращення пускових характеристик та зменшення втрат енергії. The article considers a compensated asynchronous machine that consists of a power active filter and an asynchronous machine switched in parallel. The starting system of the asynchronous machine is set at the nominal voltage of 380 V and power of 75 kW. An equivalent circuit of the system is given, time diagrams of voltage and currents in the system are built for starting of the asynchronous machine with and without the power active filter.